Costs of First-Line Treatment With FOLFIRINOX, Modified FOLFIRINOX, and Gemcitabine With Nab-Paclitaxel in Metastatic Pancreatic Ductal Adenocarcinoma - Syvart Dennen; Marty Masek; Paul Cockrum; Elizabeth Nagelhout; Ravi Paluri (Journal of Health Economics and Outcomes Research)
# Background Further research is needed to determine real-world costs of first-line (1L) treatment of metastatic pancreatic ductal adenocarcinoma (mPDAC) with FOLFIRINOX (FFX), modified FFX (mFFX), and gemcitabine with nab-paclitaxel (GnP).